Collagen Supplements for Aging and Wrinkles: A Paradigm Shift in the Field of Dermatology and Cosmetics - Hend Al-Atif (Mattioli1885, 2022)
Introduction: Slowing the aging process by use of collagen supplements has become a driving force in the field of dermatology and cosmetics. Generally, oral and topical collagen are used in anti-aging products, as reported in the literature. Objectives: The overarching goal of this research is to collate the consequences of oral collagen with those of topical collagen in reducing or delaying the aging process. Methods: We executed an electronic search in Google Scholar and PubMed. We considered a study eligible if it was original research, published in English between 2010 and 2020, and if it provided information on the topic of collagen and aging. We retrieved 12 full-text articles, and these were assessed by reviewers independently. Results: All human studies included in the review were randomized controlled trials mainly conducted in high- to middle-income countries which highlighted that both oral and topical collagen supplements help to delay the aging process, with no differences arising between the two types of collagen. The evidence from the reviewed studies suggested that both collagen supplements improve skin moisture, elasticity, and hydration when orally administered. Additionally, collagen reduces the wrinkling and roughness of the skin, and existing studies have not found any side effects of its oral supplements. Conclusions: Both oral and topical collagen can contribute to reducing or delaying skin aging. Future epidemiological studies with large sample sizes and thorough follow-up measures would be required to comprehensively understand the potential effects of these two types of collagen on the aging process.